A highly potent anti-VISTA antibody KVA12123 - a new immune checkpoint inhibitor and a promising therapy against poorly immunogenic tumors - Iadonato, Shawn; Ovechkina, Yulia; Lustig, Kurt; Cross, Jessica; Eyde, Nathan; Frazier, Emily; Kabi, Neda; Katz, Chen; Lance, Remington; Peckham, David; Sridhar, Shaarwari; Talbaux, Carla; et al. (Frontiers in Immunology, 2023)
Background: Immune checkpoint therapies have led to significant breakthroughs in cancer patient treatment in recent years. However, their efficiency is variable, and resistance to immunotherapies is common. VISTA is an immune-suppressive checkpoint inhibitor of T cell response belonging to the B7 family and a promising novel therapeutic target. VISTA is expressed in the immunosuppressive tumor microenvironment, primarily by myeloid lineage cells, and its genetic knockout or antibody blockade restores an efficient antitumor immune response.Methods: Fully human monoclonal antibodies directed against VISTA were produced after immunizing humanized Trianni mice and single B cell sequencing. Anti-VISTA antibodies were evaluated for specificity, cross-reactivity, monocyte and T cell activation, Fc-effector functions, and antitumor efficacy using in vitro and in vivo models to select the KVA12123 antibody lead candidate. The pharmacokinetics and safety profiles of KVA12123 were evaluated in cynomolgus monkeys.Results: Here, we report the development of a clinical candidate anti-VISTA monoclonal antibody, KVA12123. KVA12123 showed high affinity binding to VISTA through a unique epitope distinct from other clinical-stage anti-VISTA monoclonal antibodies. This clinical candidate demonstrated high specificity against VISTA with no cross-reactivity detected against other members of the B7 family. KVA12123 blocked VISTA binding to its binding partners.KVA12123 treatment mediated strong single-agent antitumor activity in several syngeneic tumor models and showed enhanced efficacy in combination with anti-PD-1 treatment. This clinical candidate was engineered to improve its pharmacokinetic characteristics and reduce Fc-effector functions. It was well-tolerated in preclinical toxicology studies in cynomolgus monkeys, where hematology, clinical chemistry evaluations, and clinical observations revealed no indicators of toxicity. No cytokines associated with cytokine release syndrome were elevated.These results establish that KVA12123 is a promising drug candidate with a distinct but complementary mechanism of action of the first generation of immune checkpoint inhibitors.